Optimized recovery of phenolic and flavonoid compounds from medicinal plant extracts for enhanced antioxidant activity: A mixture design approach - Faiza Imtiaz; Dildar Ahmed; Osama A. Mohammed; Umer Younas; Munawar Iqbal (Results in Chemistry)
The current study was carried out to compare total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activities of extracts/ fractions of nine medicinal plants including Quercus infectoria (QI), Fagonia arabica (FA), Embelia ribes (ER), Cichorium intybus (CI), Ipomoea nil (IN), Acacia nilotica (AN), Psoralea corylifolia (PC), Tinospora cordifolia (TC), and Thuja orientalis (TO). Chloroform and ethyl acetate fractions obtained from QI, ER, AN, PC, and TO were found to have the highest phenolic/flavonoid content and antioxidant index values. The chloroform fraction of QI exhibited the highest DPPH and ABTS activities with 77.63% and 97.94%, respectively. Based on these results, the three highest-ranked plant extracts were further investigated using a simplex centroid mixture design. The optimal blend, consisting of 69% QI, 12% TO, and 19% ER, resulted in maximized values for TPC (292.36 mg GAE/g DW), TFC (65.21 mg RE/g DW), and DPPH (90.44%). This study highlights the development of optimized plant extract mixtures as a natural therapeutic strategy specifically designed to combat oxidative stress-related diseases, offering a potential alternative to conventional treatments.